The structural response and manner of progressive collapse in RC buildings under the blast and Provide approaches to retrofitting columns against blast - GholamReza Havaei (Iranian Society of Structrual Engineering (ISSE), 2017)
In accidents caused by explosion, the initial damage is usually caused by direct hit blast that it causes damage and serious destruction of structural components. In this state, the collapse of structural components and the subsequent progressive collapse may cause an increase in damages and eventually collapse of the structure. On the other hand, observations show that most of these buildings designed and built without consideration of their vulnerability to such events. In this study, global and local response of reinforced concrete buildings and their damages evaluated against explosion. First the global stability of building using SAP2000 is evaluated against explosion and then the amount and behaviour of damages in The key structural components of the building after the explosion is investigated using LS DYNA. The study involved four important areas in structural engineering that includes blast load determination, numerical modelling with FEM techniques, material performance under high strain rate and non-linear dynamic analysis. Two types of design methods are recommended for RC columns to provide superior residual capacities. They are RC columns detailing with additional steel reinforcement cages and a composite columns including a central structural steel core. The results showed that the use of this type of columns compared to typical RC column against explosion can have a significant impact in increasing the bearing capacity of structural components against gravity loads after the explosion.